Assessment of non-directed computer-use behaviours in the home can indicate early cognitive impairment: A proof of principle longitudinal study. (2nd January 2023) - Stringer, Gemma; Couth, Samuel; Heuvelman, Hein; Bull, Christopher; Gledson, Ann; Keane, John; Rayson, Paul; Sutcliffe, Alistair; Sawyer, Peter Harvey; Zeng, Xiao-Jun; Montaldi, Daniela; Brown, Laura J. E.; et al.
Abstract: Objectives: Computer-use behaviours can provide useful information about an individual's cognitive and functional abilities. However, little research has evaluated unaided and non-directed home computer-use. In this proof of principle study, we explored whether computer-use behaviours recorded during routine home computer-use i) could discriminate between individuals with subjective cognitive decline (SCD) and individuals with mild cognitive impairment (MCI); ii) were associated with cognitive and functional scores; and iii) changed over time. Methods: Thirty-two participants with SCD ( n = 18) or MCI ( n = 14) (mean age = 72.53 years; female n = 19) participated in a longitudinal study in which their in-home computer-use behaviour was passively recorded over 7–9 months. Cognitive and functional assessments were completed at three time points: baseline; mid-point (4.5 months); and end point (month 7 to 9). Results: Individuals with MCI had significantly slower keystroke speed and spent less time on the computer than individuals with SCD. More time spent on the computer was associated with better task switching abilities. Faster keystroke speed was associated with better visual attention, recall, recognition, task inhibition, and task switching. No significant change in computer-use behaviour was detected over the study period. Conclusion: Passive monitoring of computer-use behaviour shows potential as an indicator of cognitive abilities, and can differentiate between people with SCD and MCI. Future studies should attempt to monitor computer-use behaviours over a longer time period to capture the onset of cognitive decline, and thus could inform timely therapeutic interventions. Supplemental data for this article can be accessed online at http://dx.doi.org/10.1080/13607863.2022.2036946